Evaluation of The Safety and Efficacy of Low Dose Atorvastatin in Bronchial Asthma - R, Geetha; Madhavan, S; Parvathavarthini, S (International Journal of Medical Research and Review, 2014)
Introduction: Statins are lipid lowering drugs with pleiotropic anti-inflammatory and immunomodulatory effects. We tested the hypothesis that short-term treatment with atorvastatin improves asthma control and airway inflammation in chronic asthma patients. Materials and Methods: This is a Prospective, Open label, Randomized, Controlled, Crossover study conducted at Stanley Medical College Hospital for 10 weeks. 60 patients with Chronic Asthma of more than 2 years duration were recruited. The patients were randomized to receive atorvastatin 10 mg daily for 4 weeks separated by a 2-week washout period in a crossover fashion. Patients continued on their usual asthma drug treatment throughout the study. The effects of atorvastatin on absolute eosinophil count (AEC), C- reactive protein (CRP), Forced Expiratory Volume in 1 sec (FEV1) were analyzed. Results: Data analysis revealed that no significant differences in forced expiratory volume in the first second (FEV1), absolute eosinophil count and C- reactive protein levels in both control and study groups. Conclusion: Our study shows atorvastatin is not effective in the treatment of chronic asthma.